KAJIAN HUKUM AKTIVITAS KEPEMUDAAN DAN KEHIDUPAN SOSIAL DI KOTA SAMARINDA” “Legal Studies Youth Activities and Social Life in Samarinda - Wahyuni Safitri (Law Department, University of Widya Gama Mahakam Samarinda, 2017)
Very important role of youth in the development process is ongoing because the youth is a segment that has great energy and innovation high that can be utilized as much as possible. Exclusion of youth in the development process will only lead to negative impacts that will hinder the development process. Necessary strategies are carried out systematically to address the complexity of youth problems both in terms of positive and negative. Increased youth participation in all aspects of human life and attention as well as engage youth in the planning, implementation, monitoring and evaluation of all policies and programs in various fields of life and the development of a strategy for the attention and experience on youth issues as an integral dimension. Some important things that underlie the study of youth which are the aspirations of young people should be no one noticed, the opportunity for young people to take greater responsibility, capacity building and empowering youth and active participation of youth in all stages of program design, implementation and evaluation.